Knowledge, Attitude and Practice on Occupational Safety and Health Awareness: An Exploratory Study in Technology Industry - Abu Bakar, Fatin Nur Najihah; Ismail , Elya Atikah; Sahak, Nurrul Hafeezah (Progress in Engineering Application and Technology, 2024)
This study aimed to assess the influence of knowledge, attitude, and practice on occupational safety and health (OSH) risk management in Malaysia. A cross-sectional study was conducted using a 30-item self-administered questionnaire addressing information on sociodemographic, knowledge on OSH, attitude and practice in OSH among workers. A total of 70 technicians participated in the survey. The mean scores of knowledge level and attitude level were found to be higher among individuals aged 50-59 years (M=4.40, SD=0.26), individuals with a working experience of 16-25 years, and those with more than 25 years of working experience. The lowest mean scores in attitude were observed among individuals in the age group 30-39 years and the second lowest was from the youngest age group, 20-29 years. The data analysis of the study found that there was no significant influence between the factors of knowledge and practice with demographic which is age, working experience, and designation, with probability values greater than p > 0.05. Furthermore, the implementation of a suitable, adequate, and continually improving system was crucial and needs to be implemented to manage OSH risks in the organization. The findings of this study were crucial in determining the organizational characteristics that can impact the effectiveness of risk management implementation to address issues, especially in Malaysian organizations.